Plankton Profile in White Shrimp Pond (L. vannamei) - ariadi - heri; Dwi Ario Fajar (Universitas Tidar, 2022)
Plankton are microscopic organisms that exist in the waters of shrimp ponds. The purpose of this study was to determine the profile of plankton dominance in white shrimp (L. vannamei) aquaculture ponds. This research was conducted using an ex-pose facto causal design method in intensive white shrimp culture ponds. The results of this study showed that in the research shrimp ponds, 4 main genera of plankton were found, namely the genus chlorophyceae consisting of species chlamydomonas sp., chlorella sp., oocystis sp., tetracelmis sp., genus cyanophyceae consisting of species anabaena sp., chroococcus sp., microcystis sp., oschillatoria sp., genus Euglenophyceae namely phacus sp. and the genus Dinophyceae which consists of the species gymnodinium sp. noctiluca sp. peridinium sp. prorocentrum sp. Overall the level of dominance of abundance and community dominance index was dominated by plankton of the genus chlorophyceae as much as 1.03E+06 cells/ml and a dominance index of 82.40%. Then from the genus chlorophyceae the dominant species is plankton species chlorella sp., with an abundance of 7.50E+05 cells/ml and a dominance index of 73%. The conclusion of this study is that plankton in the research ponds are dominated by the genus chlorophyceae which consists of dominant species of chlorella sp and chlamydomonas sp, oocystis sp, tetracelmis sp which are predominant.